CD73 in small extracellular vesicles derived from HNSCC defines tumour‐associated immunosuppression mediated by macrophages in the microenvironment. Issue 5 (6th May 2022) - Lu, Tingwei; Zhang, Zhen; Zhang, Jianjun; Pan, Xinhua; Zhu, Xueqin; Wang, Xu; Li, Zhihui; Ruan, Min; Li, Huasheng; Chen, Wantao; Yan, Ming
Abstract: Research on tumour cell‐derived small extracellular vesicles (sEVs) that regulate tumour microenvironment (TME) has provided strategies for targeted therapy of head and neck squamous cell carcinoma (HNSCC). Herein, we demonstrated that sEVs derived from HNSCC cancer cells carried CD73 (sEVs CD73 ), which promoted malignant progression and mediated immune evasion. The sEVs CD73 phagocytosed by tumour‐associated macrophages (TAMs) in the TME induced immunosuppression. Higher CD73 high TAMs infiltration levels in the HNSCC microenvironment were correlated with poorer prognosis, while sEVs CD73 activated the NF‐κB pathway in TAMs, thereby inhibiting immune function by increasing cytokines secretion such as IL‐6, IL‐10, TNF‐α, and TGF‐β1. The absence of sEVs CD73 enhanced the sensitivity of anti‐PD‐1 therapy through reversed immunosuppression. Moreover, circulating sEVs CD73 increased the risk of lymph node metastasis and worse prognosis. Taken together, our study suggests that sEVs CD73 derived from tumour cells contributes to immunosuppression and is a potential predictor of anti‐PD‐1 responses for immune checkpoint therapy in HNSCC.